THE IMPORTANCE OF COMPETENCY, MOTIVATION AND TALENT MANAGEMENT TOWARDS THE EMPLOYEES PERFORMANCE AT BUDI KEMULIAAN HOSPITAL - Arsa Priyo Rahardjo; Mafizatun Nurhayati (Dinasti Publisher, 2022)
This research aims to reveal the importance of competence,motivational and talent management in affecting the employee performance. This research population was the employees of Budi Kemuliaan Hospital from the nurse or midwife division, medical staff and non-medical staff which located in DKI Jakarta, with a total sample of 98 respondents. Through purposive sampling, those population were permanent employees in the nurse or midwife department, medical staff and non-medical division who have been worked for more than 2 years in order to gain their respective performance well. The analytical method that applied in this research by multiple linear regression with the assist of SPSS program. The research outcomes has been proved that competence has a positive affect on employee performance. So does with Motivation which also has a positive impact towards it. The increasing in competence and motivation on nurses or midwives, medical staff, and non-medical staff would be able to lifted their performance as well. However, it was found that the talent management has no impact towards the employee performance. This could be said that no matter how good talent management is, it would not be able to boost the employee performance, therefore further research are needed.